CHARACTERISTICS OF OLOKIZUMAB PHARMACOKINETICS IN PATIENTS WITH NOVEL CORONAVIRUS INFECTION COVID-19 - E. V. Tavlueva; E. V. Zernova; M. P. Kutepova; N. E. Kostina; V. S. Lesina; D. R. Mould; K. Ito; A. V. Zinchenko; A. N. Dolgorukova; M. V. Nikolskaya; M. S. Lemak; O. V. Filon; et al. (Фармация и фармакология (Пятигорск))
The aim of the article is to study pharmacokinetic characteristics of intravenous olokizumab in patients with moderate COVID-19 to relieve a hyperinflammation syndrome.Materials and methods. The pharmacokinetic study was conducted as a part of a phase III clinical study (RESET, NCT05187793) on the efficacy and safety of a new olokizumab regimen (intravenous, at the doses of 128 mg or 256 mg) in COVID-19 patients. Plasma concentrations of olokizumab were determined by the enzyme immunoassay. The population analysis was performed using a previously developed pharmacokinetic model based on a linear two compartment.Results. The pharmacokinetic analysis included the data from 8 moderate COVID-19 patients who had been administrated with olokizumab intravenously at the dose of 128 mg. According to the analysis results in this population, there was an increase in the drug clearance, compared with the data obtained in healthy volunteers and the patients with rheumatoid arthritis: 0.435, 0.178 and 0.147 l/day, respectively. The parameters analysis within the framework of a population pharmacokinetic model showed that the main factors for the increased olokizumab clearance are a high body mass index. In addition, the presence of COVID-19 itself is an independent factor in increasing the drug clearance.Conclusion. After the intravenous olokizumab administration, an increase in the drug clearance is observed in moderate COVID-19 patients against the background of the disease course. The main contribution to the increased clearance is made by the characteristics of the population of COVID-19 patients associated with the risk of a severe disease and inflammation. When administered intravenously at the dose of 128 mg, a therapeutically significant olokizumab level was maintained throughout the acute disease phase for 28 days.